Basic semen parameters assisted by Computer-Aided sperm analysis (CASA) and their correlations with advanced semen parameters in normozoospermic men with different abstinence periods - Ayad, Bashir Mohamed (Stellenbosch : Stellenbosch University, 2018)
Thesis (PhD)--Stellenbosch University, 2018.